Concept of innovation in low-income market - Nogami, Vitor Koki da Costa; Vieira, Francisco Giovanni David; Veloso, Andres Rodriguez (Review of Business Management, 2017)
Purpose – Investigate the concept and the adoption of innovation in the low-income market. Design/methodology/approach – Four different studies were conducted. First, a Delphi study with 126 Marketing and Innovation professors from graduate programs. Second, interviews with 13 professionals, technical assistance professionals and retail managers. Third, two focus groups with low-income consumers. Fourth, survey with 390 respondents. Findings – The results indicate that innovations in the low-income markets are mainly characterized by adaptations and adjustments in products, with emphasis on incremental innovations, not radical. In addition, the adoption of innovation in this context is characterized as late, not initial. Originality/value – In terms of theoretical contributions, the present study reveals how the concept of innovation is built in the low-income market. From a perspective collectively constructed with information from different market agents (industry, retail and consumers), research findings become robust to understanding a phenomenon. Moreover, in addition to different market agents, different methods of data collection and analysis were also used, further enriching the results. This collective contribution, based theoretically on a literature of social construction, interviewing different market agents and using different methodological approaches, synergistically potentiated the development of this paper.